Hubungan Peran Suami Dan Orangtua Dengan Perilaku Ibu Hamil Dalam Pelayanan Antenatal Dan Persalinan Di Wilayah Puskesmas Kecamatan Sedan Kabupaten Rembang - Hafidz, Effi M (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2007)
Background : Maternal mortality rate (MMR) in Central Java is still very high. It is around 250 to 300 per 100.000 child births. The higher MMR in Indonesia is mostly caused by bleeding, infection and eclampsia and other disease complications that have been suffered before and during pregnancy of the women. Improving community participation particularly husband and parent, to support antenatal care and delivery care of their pregnant women, might be expected to reduce maternal mortality rate.Method : This study aims to identify the relationship between the role of husband and parent in supporting to visit health personnel (at least midwife) for antenatal care and delivery care of pregnant women and their behaviour. This study employs a cross-sectional survey with 87 samples of pregnant women. Face to face interview was employed to collect data from the respondents. Triangulation was employed by using indepth interviews to husband and parents to confirm their roles. Quantitative data was analysed using Chi-square and logistic regression test and content analysis was used to analyse qualitative data.Results : The study shows that there was significant relationship between the role of husband and behaviour of pregnant mothers in antenatal care and delivery (p: 0.000). Likewise, the role of parent has also significant relationship with behaviour of pregnant mothers (p:0.000). Logistic regression test indicated that the role of husband’s support has more influence than parent’s for both antenatal and delivery care. The study suggests that midwife and other health personnel need to provide information to husbands in order to socialize their role in antenatal and delivery care programmes.Keywords : role of husband, parents, behaviour of women, antenatal and delivery care.